The tankyrase‐specific inhibitor JW74 affects cell cycle progression and induces apoptosis and differentiation in osteosarcoma cell lines. (17th December 2013) - Wessel Stratford, Eva; Daffinrud, Jeanette; Munthe, Else; Castro, Russell; Waaler, Jo; Krauss, Stefan; Myklebost, Ola
Abstract: Wnt/ β ‐catenin is a major regulator of stem cell self‐renewal and differentiation and this signaling pathway is aberrantly activated in a several cancers, including osteosarcoma (OS). Attenuation of Wnt/ β ‐catenin activity by tankyrase inhibitors is an appealing strategy in treatment of OS. The efficacy of the tankyrase inhibitor JW74 was evaluated in three OS cell lines (KPD, U2OS, and SaOS‐2) both at the molecular and functional level. At the molecular level, JW74 induces stabilization of AXIN2, a key component of the β ‐catenin destruction complex, resulting in reduced levels of nuclear β ‐catenin. At the functional level, JW74 induces reduced cell growth in all three tested cell lines, in part due to a delay in cell cycle progression and in part due to an induction of caspase‐3‐mediated apoptosis. Furthermore, JW74 induces differentiation in U2OS cells, which under standard conditions are resistant to osteogenic differentiation. JW74 also enhances differentiation of OS cell lines, which do not harbor a differentiation block. Interestingly, microRNAs (miRNAs) of the let‐7 family, which are known tumor suppressors and inducers of differentiation, are significantly upregulated following treatment with JW74. We demonstrate for the first time that tankyrase inhibition triggers reduced cell growth and differentiation of OS cells. This may in part be due to an induction of let‐7 miRNA. The presented data open for novel therapeutic strategies in the treatment of malignant OS. Abstract : The tankyrase inhibitor JW74 reduces Wnt/ β ‐catenin signaling in osteosarcoma (OS) cell lines, affecting growth rates and inducing differentiation of poorly differentiated OS cells. Tankyrase inhibition thus represents a novel therapeutic strategy in the treatment of OS.